Threat of non-native crayfish introductions into Turkey: global lessons - Harlioglu, Muzaffer Mustafa; Harlioglu, Ayse Gul (Springer, 2006)
Introductions of crayfish species from their home range to new environments have been carried out in many parts of the world. The most important introduced crayfish species are Procambarus clarkii, Pacifastacus leniusculus, Cherax destructor, C. quadricarinatus, Orconectes limosus, O. rusticus and Astacus leptodactylus. The environmental impact of crayfish introductions can be positive, negative or neutral. However, native crayfish populations in Europe have been negatively affected by introductions of non-indigenous crayfish species from America. Negative effects of non-native crayfish introductions included displacement of native crayfish species, transfer of disease (crayfish plague), consumption of fish eggs, reduction of fish stocks, consumption of large amounts of macrophytes, indirect and direct effects on other invertebrates and upsetting production in rice fields. As a result of non-native crayfish introductions, the natural harvest and crayfish industry in Europe have been severely affected. Large quantities of Turkish A. leptodactylus were harvested (approximately 7,000 tonnes annually) and exported to Europe before the crayfish plague was observed in these populations. The total harvest of A. leptodactylus in Turkey reduced dramatically to 320 in 1991 after the plague. Therefore, although Turkey currently has no known non-native crayfish species, there is a threat of non-native crayfish introduction in order to increase crayfish productions and subsequent harvest. The North American spiny-cheek crayfish, O. limosus, has been spreading quickly down the River Danube and could soon reach neighboring countries including Turkey. The North American signal crayfish, P. leniusculus is known from Greece and could be a threat to native stocks if it is introduced into Turkey for aquaculture. Additional threats may come from the release of other North American species, which are widely available through the aquarium trade. We conclude that the spread of non-native crayfish introductions throughout Turkey will increase local problems, because introductions of non-native crayfish in many parts of the world have been known to have caused important reductions in population density and numbers of native crayfish species. Furthermore, freshwater ecosystems may be altered by such introductions and the economic viability of native crayfish species fisheries could be severely reduced in Turkey.
Keywords: aquaculture; crayfish; harvest; introduction; native; non-native; production; Turkey